Influence of airway trolley organization on efficiency and team performance: A randomized, crossover simulation study. Issue 1 (17th October 2022) - Sturesson, Louise W.; Persson, Karolina; Olmstead, Richard; Bjurström, Martin F.
Abstract: Background: Failed management of unanticipated difficult airway situations contributes to significant anesthesia‐related morbidity and mortality. Optimization of design and layout of difficult airway trolleys (DATs) may influence outcomes during airway emergencies. The main objective of the current study was to evaluate whether a difficult airway algorithm‐based DAT with integrated cognitive aids improves efficiency and team performance in difficult airway scenarios. Methods: In a crossover design, 16 teams (anesthetist, nurse anesthetist, assistant nurse) completed two high‐fidelity simulated unanticipated difficult airway scenarios. Teams used both an algorithm‐based DAT and a comparison, standard DAT, in the scenarios and were randomized to order of trolley type. Outcome measures included objective efficiency parameters, team performance assessment and subjective user‐ratings. Linear mixed models ANOVA, including DAT type and order of condition as main factors, was utilized for the primary analyses of the team results. Results: Usage of the algorithm‐based DAT was associated with fewer departures from the difficult airway algorithm ( p  = .010), and reduced number of unnecessary drawer openings ( p  = .002), but no significant differences in time to retrieval of airway devices or time to first effective ventilation, compared to the standard DAT. There were no significant differences in team performance, although participants expressed strong preference for the algorithm‐based DAT (all user‐rated measures p  < .0001). Higher percentage of female members of the team improved adherence to the difficult airway algorithm ( p  = .043). Conclusions: Algorithm‐based DATs with integrated cognitive aids may improve efficiency in difficult airway situations, compared to traditional DATs. These findings have implications for improvement of anesthetic practice.